2002
DOI: 10.1021/ja0168763
|View full text |Cite
|
Sign up to set email alerts
|

α-l-ribo-Configured Locked Nucleic Acid (α-L-LNA):  Synthesis and Properties

Abstract: The syntheses of monomeric nucleosides and 3'-O-phosphoramidite building blocks en route to alpha-L-ribo-configured locked nucleic acids (alpha-L-LNA), composed entirely of alpha-L-LNA monomers (alpha-L-ribo configuration) or of a mixture of alpha-L-LNA and DNA monomers (beta-D-ribo configuration), are described and the alpha-L-LNA oligomers are studied. Bicyclic 5-methylcytosin-1-yl and adenine-9-yl nucleoside derivatives have been prepared and the phosphoramidite approach has been used for the automated olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 57 publications
4
112
0
Order By: Relevance
“…Interestingly, incorporation of the corresponding C5-functionalized LNA or a-l-LNA building blocks into ONs results in similar destabilization of duplexes although with reduced sequence variability (DT m between À2.0 and À4.5 8C for monomer Y, and between À2.5 and À4.0 8C for monomer Z, Table 1). Thus, the well-established stabilizing effects of conventional LNA [11] and a-l-LNA [12] monomers appear to be fully compromised by the 3-(1-pyrenecarboxamido)propynyl moiety www.chemeurj.org at the C5 position. This contrasts trends with C5-functionalized LNA carrying non-aromatic moieties, which generally are very well tolerated in nucleic acid duplexes.…”
Section: Thermal Denaturation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, incorporation of the corresponding C5-functionalized LNA or a-l-LNA building blocks into ONs results in similar destabilization of duplexes although with reduced sequence variability (DT m between À2.0 and À4.5 8C for monomer Y, and between À2.5 and À4.0 8C for monomer Z, Table 1). Thus, the well-established stabilizing effects of conventional LNA [11] and a-l-LNA [12] monomers appear to be fully compromised by the 3-(1-pyrenecarboxamido)propynyl moiety www.chemeurj.org at the C5 position. This contrasts trends with C5-functionalized LNA carrying non-aromatic moieties, which generally are very well tolerated in nucleic acid duplexes.…”
Section: Thermal Denaturation Studiesmentioning
confidence: 99%
“…Calculations suggest that the bicyclic skeletons of LNA and a-l-LNA monomers Y and Z influence the glycosidic torsional angle profile leading to altered positional control and photophysical properties of the C5-fluorophore. Keywords: bicyclic nucleotides · BNA · DNA targeting · pyrene · single nucleotide polymorphisms As part of our ongoing interest in functionalized variants [10] of LNA (Locked Nucleic Acid) [11] and a-l-LNA, [12] we set out to synthesize and characterize the corresponding C5-functionalized LNA and a-l-LNA monomers Y and Z in a comparative study with monomer X (Figure 1). We hypothesized that the extreme sugar puckering of the bicyclic LNA and a-l-LNA nucleotides [13] would a) influence the anti to syn rotational profile due to steric hindrance between H6 and sugar protons (Figure 1), b) result in higher positional control of the polarity-sensitive 3-(1-pyrenecarboxamido)propynyl fluorophore, and c) possibly lead to improved SNP-typing properties.…”
Section: Introductionmentioning
confidence: 99%
“…One LNA diastereoisomer, namely a-L-LNA, has been studied intensively and has shown very efficient recognition of complementary strands, in particular complementary RNA [19,22,23,26,28,29]. Accordingly, incorporation of three 2'-O,4'-C-methyleneot-L-ribofuranosyl thymine ot-L-LNA monomers into either a DNA strand [28] (cf., entry 9, ot-L-LNA/DNA chimera) or a 2'-OMe-RNA strand [26] (cf., entry 10, ot-L-LNA/2'-OMe-RNA chimera) lead to significantly increased Tm values.…”
Section: Hybridization Characteristics Of Lna Oligonucleotidesmentioning
confidence: 99%
“…On the basis of these results, we speculate that the mechanism of inhibition of resistance to AMK is interference with ribosome assembly and/or steric hindrance of translation. Although we cannot discount a level of contribution of RNase H-mediated mRNA degradation, previous results obtained testing LNA-DNA co-oligomers with various configurations that showed that only gapmers with at least 6 contiguous deoxynucleotides induce significant RNase H activity (48)(49)(50) would discourage interpretation of this as a significant mechanism.…”
Section: Discussionmentioning
confidence: 81%